A RARE, LIFE-THREATENING COMPLICATION OF ACUTE URINARY TRACT INFECTION - Tjaša Šinkovec Savšek; Rina Rus (The Society for Children with Metabolic Disorders, 2023)
Urinary tract infections are one of the most common bacterial infections in children and are often the first sign of congenital anomalies of the kidney and urinary tract. When detected early and treated correctly, complications are rare. In the acute stage of the infection, a rare but life-threatening complication - pseudohypoaldosteronism - can occur. It usually affects children up to six months of age. In this article, we describe the clinical case of a six-month-old boy who developed secondary pseudohypoaldosteronism type 1 following an acute urinary tract infection. In addition, we discuss the clinical picture, diagnostics, differential diagnosis, and treat-ment of secondary pseudohypoaldosteronism type 1, which occurs due to urinary tract infection and congenital abnormalities of the urinary tract.